Researching Lay Perceptions of Inequality through Images of Society: Compliance, Inversion and Subversion of Power Hierarchies - Vanke, Alexandrina (Sociology (Oxford), 2024)
Increased inequalities around the globe have led social researchers to invent innovative methodologies to study how people subjectively perceive inequality and imagine society. This article presents the development of an arts-informed method, ‘drawing of society’, applied to a multi-sited ethnography of everyday inequalities in two major post-industrial cities of Russia. It contributes to the debate on lay perceptions of social structure by looking at moral and symbolic signifiers of inequality. Building on multi-sensory data, I argue that workers and professionals tend to imagine Russian society as divided between a small group of the rich and a large group of the poor and as consisting of social classes. Ordinary people self-identify with the poor and perceive their position as being at the bottom of the social hierarchy. Depending on their lived experiences, research participants express their sense of inequality through the narrative strategies of compliance, inversion and subversion of power hierarchies.